Товарна політика як інструмент формування конкурентних переваг у міжнародному маркетингу - Решетнікова, Ольга Валеріївна; Reshetnikova, Olha; Даниленко, Вікторія Іванівна; Danylenko, Viktoriia; Богоутдінова А. М.; Bohoutdinova A. M. (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У статті розглянуто товарну політику як стратегічний інструмент міжнародного маркетингу, що визначає конкурентні можливості підприємств у глобалізованому середовищі. Показано, що формування асортименту, управління якістю, брендинг, інновації та адаптація продукції до специфіки різних країн стають ключовими чинниками довгострокового успіху на світових ринках. Виокремлено відмінності між внутрішньою та міжнародною товарною стратегією. Обґрунтовано важливість урахування соціокультурних особливостей і поведінкових моделей споживачів, що визначають рівень сприйняття продукції та лояльність до бренду. Підкреслено зростаючу роль цифрових технологій у персоналізації товарів, прогнозуванні попиту й підвищенні ефективності комунікацій. Запропоновано практичні орієнтири для вдосконалення товарної політики підприємств на міжнародному ринку, зокрема диверсифікацію асортименту, активну інтеграцію інновацій, посилення брендової ідентичності та побудову гнучких бізнес-моделей, здатних швидко реагувати на зміни середовища. /// EN: The article explores the role of product policy as a strategic instrument for creating competitive advantages in international marketing. Its relevance is determined by growing global competition, rapid digitalization, and the need for companies to adapt to diverse cultural, economic, and regulatory environments. The aim of the study is to enhance theoretical understanding of product policy in the context of globalization and to substantiate practical approaches that strengthen enterprise competitiveness in foreign markets. The methodological basis involves systemic and comparative analysis, synthesis, and generalization, which make it possible to reveal the functions of product policy, its influence on international business, and directions for adaptation under global challenges. The results demonstrate that product policy is not limited to managing assortment or product quality but becomes a comprehensive strategic tool that integrates innovation, branding, lifecycle management, and product positioning. Particular emphasis is placed on the adaptability of companies, which must balance standardization and localization of their product lines, while at the same time responding flexibly to external challenges such as political instability, cultural differences, and technological change. The study highlights that product adaptation enhances consumer loyalty and market acceptance, while digital tools such as big data and artificial intelligence improve demand forecasting, personalization, and product portfolio management. Cultural and social factors, including traditions, value systems, and behavior models, are identified as crucial for shaping brand perception in global markets. The practical value of the article lies in recommendations for improving product policy in international marketing: diversifying product lines with regard to local specifics, integrating innovations and sustainability, strengthening brand strategies, and expanding the use of digital technologies. These measures enable enterprises to consolidate their positions, enter new markets, and achieve long-term business sustainability.
Product policy as a tool for shaping competitive advantages in international marketing
Keywords: товарна політика; міжнародний маркетинг; конкурентні переваги; адаптація продукції; цифрові технології; product policy; international marketing; competitive advantages; product adaptation; digital technologies